Holistic Islamic Moderation Education: The Contribution of Balanced Thinking in Combating Religious Radicalism - Primarni, Amie; Makmudi; Mowafg Masuwd; Nabila Yusof; Asep Nuhdi (TADRIS: Jurnal Pendidikan Islam, 2025)
This study examines the effectiveness of a holistic approach in implementing religious moderation education to cultivate balanced thinking and tolerant attitudes among students within the domain of Islamic education. Grounded in Islamic values that emphasize moderation, inclusivity, justice, and intellectual equilibrium, the research employs a qualitative phenomenological design to explore the lived experiences of students, teachers, principals, and parents in schools that explicitly adopt a holistic-based moderation framework. Data were collected through semi-structured interviews, classroom observations, and systematic document analysis, and were analyzed thematically to identify recurring meanings, patterns, and contextual interpretations. The findings indicate that integrating intellectual, emotional, social, and spiritual dimensions significantly contributes to the development of inclusive, empathetic, dialogical, and critically reflective learners. Instructional practices such as project-based learning, cross-cultural engagement, collaborative inquiry, and value-oriented dialogue effectively connect cognitive, affective, and psychomotor domains in meaningful learning experiences. Teachers play a pivotal role in modeling moderation values and facilitating participatory learning environments that strengthen emotional intelligence, mutual respect, and social cohesion within diverse classrooms and communities. The study further demonstrates that holistic moderation education positively influences students’ character formation, interpersonal competence, ethical awareness, and religious maturity, enhancing their resilience against radical, intolerant, and exclusionary ideologies in contemporary societies and educational contexts. Despite its context-bound scope and interpretive nature, this research proposes an integrated conceptual framework that bridges academic achievement and character development, offering theoretical enrichment and practical guidance for educators and policymakers seeking to design inclusive education models that promote tolerance and prevent extremism in pluralistic societies globally.